It Is Time to Revitalize the Antibiotic Pipeline: Systems Ecology Can Help - BECEREN, AYFER (MARY ANN LIEBERT, INC, 2020)
Antimicrobials have been known for millennia, but innovative antibiotics are currently in short supply. New antimicrobial discoveries are being threatened by planetary scale loss of biodiversity that has important impacts on species and ecosystems. This expert review underscores that microorganisms in nature and their diversity are essential cornerstones to revitalize the antibiotic innovation and discovery pipeline. The recent rise of systems ecology and planetary health offers new and actionable potentials in this regard. Without a systems scale focus and appreciation of systems ecology, the global threats to human and planetary health from inappropriate use of antibiotics and antimicrobial resistance will continue to escalate with serious consequences to all life on the planet. With acutely pressing research and development needs to revitalize antibiotic treatment and novel diagnostic tools for personalized medicine, national health systems ought to work across knowledge silos not only within but also across the ministries, for example, health, agriculture, environment, economy, trade, and social services ministries that collectively impact on systems ecology and by extension on health innovations including the antibiotic discovery pipeline. Such systems vision can also help to revitalize antibiotic discovery pipeline as most antibiotics have natural origins or have designs inspired or based on molecules in the environment and microorganisms that produce antibiotics. Above all, our audience and responsibility include every person who has an interest in his or her own health, in the health of his or her fellow human beings and all life on the planet, and in the health of future generations.
Keywords: antibiotics; systems ecology; national innovation systems; systems pharmacy; drug discovery; planetary health; IMPACT; ASSOCIATION; RESISTANCE; DATABASE; EVENTS; EUROPE; UNIT